Reflective Learning sebagai Pendekatan Alternatif dalam Meningkatkan Kualitas Pembelajaran dan Profesionalisme Guru Pendidikan Agama Islam - Khodijah, Nyayu (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
A professional teacher not only serves as a teacher, but also as a coach, counselor, facilitators, and managers. In order to perform all these functions, teachers are required to have certain qualifications and competence. One of the competences is competent to apply the various approaches, strategies, methods, and techniques that teach creative learning in subjects taught. This paper attempts to offer an alternative approach that is independently developed by the author and has been tested in its application of PAI learning, which is reflective learning. Reflective learning can help learners improve their understanding and awareness of Islamic values learned through learning activities which involve the process of reflection. Application of reflective learning approach has been proven to improve the success of PAI learning in schools characterized by increased religiosity of students, both in terms of effectiveness, efficiency, and attractiveness.